Metabolic Syndrome and Cognitive Function in Midlife. (5th December 2020) - Foret, Janelle T; Oleson, Stephanie; Hickson, Brennan; Valek, Stephanie; Tanaka, Hirofumi; Haley, Andreana P
Abstract: Objective: Metabolic syndrome (MetS) is a cluster of cardiovascular risk factors associated with cognitive decline. We investigated the relationship between MetS and cognition in middle-aged adults. We hypothesized that higher numbers of MetS components will relate to poorer performance on executive function (EF) tasks as frontal lobe regions critical to EF are particularly vulnerable to cardiovascular disease. Methods: 197 adults (ages 40–60) participated. MetS was evaluated using established criteria. Composite scores for cognitive domains were computed as follows: Global cognitive function (subtests from the Wechsler Abbreviated Scale of Intelligence, 2nd Edition), EF (Stroop Color Word, Digit Span Backward, and Trails A and B), and memory (California Verbal Learning Test, 2 Edition). Results: Higher number of MetS components was related to weaker EF— F (4, 191) = 3.94, p = .004, MetS components ß = −.14, p = .044. A similar relationship was detected for tests of memory— F (4, 192) = 7.86, p < .001, MetS components ß = −.15, p = .032. Diagnosis of MetS was not significantly associated with EF domain score (ß = −.05, p = .506) but was significantly associated with memory scores— F (4, 189) = 8.81, p < .001, MetS diagnosis ß = −.19, p = .006. Conclusions: Our findings support prior research linking MetS components at midlife to executive dysfunction and demonstrate that MetS, and its components are also associated with poorer memory function. This suggests that cognitive vulnerability can be detected at midlife. Interventions for MetS at midlife could alter cognitive outcomes.